2022
DOI: 10.25259/sni_264_2022
|View full text |Cite
|
Sign up to set email alerts
|

11C-methionine- and 18F-FDG-PET double-negative metastatic brain tumor from lung adenocarcinoma with paradoxical high 18F-FDG uptake: A case report

Abstract: Background: Imaging with 18F-fluorodeoxyglucose (FDG)-positron emission tomography (PET) and 11C-methionine (MET)-PET can delineate primary and metastatic brain tumors. Lesion size affects the sensitivity of both scans and histopathological features can also influence FDG-PET, but the effects on MET-PET have not been elucidated. Case Description: We report an unusual case of metastatic brain tumors without accumulation of FDG or MET, contrasting with high FDG uptake in the primary lung lesion. The brain le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This showed that the T1/T2 mismatch was not always reliable in excluding the possibility of recurrence [ 10 , 13 ]. In contrast, the increased uptake of 11 C-Met-PET was useful for estimating pathology [ 16 ]. Anti-cancer medication was not consistently administered in the present case because of IPF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This showed that the T1/T2 mismatch was not always reliable in excluding the possibility of recurrence [ 10 , 13 ]. In contrast, the increased uptake of 11 C-Met-PET was useful for estimating pathology [ 16 ]. Anti-cancer medication was not consistently administered in the present case because of IPF.…”
Section: Discussionmentioning
confidence: 99%
“…Given the relatively high dose prescribed to the tumor and the T1/T2 mismatch, tumor progression (≥20% and/or ≥5 mm enlargement following the nadir response of an enhancing lesion) was deemed to mainly reflect ARE [4,10,13]. However, because tumor recurrence could not be excluded regarding the progressive enlargement of the enhancing lesion, 11 C-methionine (Met) positron emission tomography (PET) was acquired at 23.1 months, which showed increased uptake over a wide area of the enhancing lesion, suggesting the existence of a viable tumor (Figure 6) [16]. Therefore, minimally invasive salvage surgery was planned considering that the impaired pulmonary function was not amenable to general anesthesia, and a total lesionectomy was performed under local anesthesia [17].…”
Section: Case Presentationmentioning
confidence: 99%